C1Q+ TPP1+ macrophages promote colon cancer progression through SETD8-driven p53 methylation - Veronica Veschi; Francesco Verona; Sebastiano Di Bella; Alice Turdo; Miriam Gaggianesi; Simone Di Franco; Laura Rosa Mangiapane; Chiara Modica; Melania Lo Iacono; Paola Bianca; Ornella Roberta Brancato; Caterina D’Accardo; et al. (Molecular Cancer)
Abstract Background In many tumors, the tumor suppressor TP53 is not mutated, but functionally inactivated. However, mechanisms underlying p53 functional inactivation remain poorly understood. SETD8 is the sole enzyme known to mono-methylate p53 on lysine 382 (p53K382me1), resulting in the inhibition of its pro-apoptotic and growth-arresting functions. Methods We analyzed SETD8 and p53K382me1 expression in clinical colorectal cancer (CRC) and inflammatory bowel disease (IBD) samples. Histopathological examinations, RNA sequencing, ChIP assay and preclinical in vivo CRC models, were used to assess the functional role of p53 inactivation in tumor cells and immune cell infiltration. Results By integrating bulk RNAseq and scRNAseq approaches in CRC patients, SETD8-mediated p53 regulation resulted the most significantly enriched pathway. p53K382me1 expression was confined to colorectal cancer stem cells (CR-CSCs) and C1Q+ TPP1+ tumor-associated macrophages (TAMs) in CRC patient tissues, with high levels predicting decreased survival probability. TAMs promote p53 functional inactivation in CR-CSCs through IL-6 and MCP-1 secretion and increased levels of CEBPD, which directly binds SETD8 promoter thus enhancing its transcription. The direct binding of C1Q present on macrophages and C1Q receptor (C1QR) present on cancer stem cells mediates the cross-talk between the two cell compartments. As monotherapy, SETD8 genetic and pharmacological (UNC0379) inhibition affects the tumor growth and metastasis formation in CRC mouse avatars, with enhanced effects observed when combined with IL-6 receptor targeting. Conclusions These findings suggest that p53K382me1 may be an early step in tumor initiation, especially in inflammation-induced CRC, and could serve as a functional biomarker and therapeutic target in adjuvant setting for advanced CRCs. Graphical Abstract